Regarding Scientific Discussion on Legal Nature of the Law Abuse - V. V. Lazariev; O. A. Zhydovtseva (Law and Safety)
The authors have analyzed the facts inherent in the equitable right that can lead to abuse of law. It has been emphasized that the legal literature has no single approach to the definition of the term of “law abuse”. However, there is a number of factors that influence the existence of such a specific phenomenon as “law abuse”.